2002
DOI: 10.1007/s10123-002-0066-z
|View full text |Cite
|
Sign up to set email alerts
|

Biology of killer yeasts

Abstract: Killer yeasts secrete proteinaceous killer toxins lethal to susceptible yeast strains. These toxins have no activity against microorganisms other than yeasts, and the killer strains are insensitive to their own toxins. Killer toxins differ between species or strains, showing diverse characteristics in terms of structural genes, molecular size, mature structure and immunity. The mechanisms of recognizing and killing sensitive cells differ for each toxin. Killer yeasts and their toxins have many potential applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
0
23

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(159 citation statements)
references
References 13 publications
4
132
0
23
Order By: Relevance
“…Yao and Tian (2005) applied the antagonist Cryptococcus laurentii to control postharvest diseases (Monilinia fructicola and Penillium expansum) in peach fruit. The cited authors noted the maximum activity levels of 1,3-glucanase and peroxidase (POD) and enhanced effects of yeasts fungi have been also observed in previous research (Marquina et al 2002;Walker et al 1995;Vero et al 2009). The studies of other authors have shown that A. pullulans isolates may produce the enzymes glucanase and chitinase in the presence of Penicillium expansum cell walls (Vero et al 2009).…”
Section: Discussionsupporting
confidence: 63%
“…Yao and Tian (2005) applied the antagonist Cryptococcus laurentii to control postharvest diseases (Monilinia fructicola and Penillium expansum) in peach fruit. The cited authors noted the maximum activity levels of 1,3-glucanase and peroxidase (POD) and enhanced effects of yeasts fungi have been also observed in previous research (Marquina et al 2002;Walker et al 1995;Vero et al 2009). The studies of other authors have shown that A. pullulans isolates may produce the enzymes glucanase and chitinase in the presence of Penicillium expansum cell walls (Vero et al 2009).…”
Section: Discussionsupporting
confidence: 63%
“…These phenotypes are: killer (K); killer-sensitive (K-S); sensitive (S); neutral (N) (Delfini and Formica, 2001). Several killer toxin types has been described for S. cerevisiae, however K2-type toxin has proved to be the most important one in winemaking because it is active at pH values during wine production (Marquina et al, 2002). In the present study, it was found that ten S. cerevisiae isolates were sensitive, four isolates were neutral, five isolates were killer-sensitive and only one isolate was killer (Table V).…”
Section: Killer Activity and Interaction With Starter Culturesupporting
confidence: 49%
“…In the search for novel and more selective antifungal agents, fungal cell wall components represent primary targets, as these structures are restricted to yeasts and higher fungi and do not occur in human cells [44,45]. Each of the mentioned cell wall components has been shown to act as the primary binding site for different yeast killer toxins [46][47][48][49]. In addition, for killer toxins secreted by various strains of the yeast Hansenula it was demonstrated that these toxins not only bind to yeast cell wall components, but that they also strongly inhibit de novo L-1,3-D-glucan biosynthesis [50,51].…”
Section: Mycoviruses and Toxinsmentioning
confidence: 99%
“…These derivatives have shown activity against various human fungal pathogenic fungi including C. albicans and may be therapeutic when administered parentally. For reviews of killer toxin/antibodies the reader is referred to Marquina et al [49], Magliani et al [55], and Schmitt and Breinig [40].…”
Section: Mycoviruses and Toxinsmentioning
confidence: 99%